GENETIC EVALUATION OF BRASSICA NAPUS FOR VARIOUS YIELD AND OIL CONTRIBUTING ATTRIBUTES - GHAFOOR, I; KANWAL, A; MAKHDOOM, M; KANWAL, S; AHSRAF, MA; AHSAN, A; GULNAZ, S; AJMAL, S; AHMAD, J; NADEEM, M; et al. (Biological and Clinical Sciences Research Journal, 2023)
Genetic components of variation were estimated for six Brassica napus lines using 6×6 diallel scheme. The current research was conducted in the winter season during 2019-20 in the Department of Plant Breeding and Genetics University of Agriculture Faisalabad. Statistical analysis exhibits great diversity among parental genotypes and F1 hybrids for all the investigated characters. All the characters under study manifested over dominance type of gene pattern excluding the number of primary branches/plants controlled by partial dominance type gene action. The traits like plant height, primary branches/plant, days to 50% flowering, and 1000 grain weight showed the highest dominant gene action exhibited by DGL. Genotype B-56 showed dominant gene action for siliquae per plant days to maturity and grain yield. ZMR-2 and ZM-RN possessed the highest number of dominant genes for the time taken flower completion and oil contents, respectively. Broad sense heritability had a high value for all traits (62%-85%), indicating that these traits can be used for further improvement.